2004
DOI: 10.1002/bjs.4615
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted distal gastrectomy for early gastric cancer in the elderly

Abstract: LDG offers particular advantages to elderly patients with early gastric cancer, including rapid return of gastrointestinal function, fewer complications and a shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
3
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 22 publications
4
50
3
1
Order By: Relevance
“…The incidence of complications classified as grade III or above in the Clavien-Dindo grading system was approximately 10 % in our cohort. This rate was relatively low and satisfactory compared with previous studies [18,19,21], especially considering that we performed radical surgery involving modified D2 lymph node dissection with curative intent. Median postoperative hospital stay (range) was 11 (7-55) days, which did not seem to be different from previously reported postoperative stay after LADG in all age groups, although statistical analysis was not performed [33].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The incidence of complications classified as grade III or above in the Clavien-Dindo grading system was approximately 10 % in our cohort. This rate was relatively low and satisfactory compared with previous studies [18,19,21], especially considering that we performed radical surgery involving modified D2 lymph node dissection with curative intent. Median postoperative hospital stay (range) was 11 (7-55) days, which did not seem to be different from previously reported postoperative stay after LADG in all age groups, although statistical analysis was not performed [33].…”
Section: Discussionsupporting
confidence: 62%
“…Several previous studies indicating the feasibility of LAG in the elderly concluded that LAG produces an incidence rate of postoperative complications in the elderly similar to that in younger patients [18][19][20][21]. However, the definition of complication severities after LAG in the elderly was not strictly defined in these previous reports.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, multi-port laparoscopic surgery (MLS) has been adopted more frequently worldwide for the treatment of colon cancer. Compared with open surgery, MLS has been associated with less pain, a quicker recovery of gastrointestinal function, improved pulmonary function, shorter hospital stays and a better postoperative quality of life (3). In addition, single-incision laparoscopic surgery (SLS) has been successfully introduced for colon cancer treatment (4)(5)(6)(7)(8), and has become a more commonly used surgical option.…”
Section: Introductionmentioning
confidence: 99%
“…Yasuda et al [30] found that LADG offerred particular advantages to elderly patients (aged 70 years or more), including rapid return of gastrointestinal function, fewer complications, and a shorter hospital stay, in comparison to open surgery.…”
Section: Ladg In Obese Patients and Elderly Patientsmentioning
confidence: 99%